ZOOPLANKTON COMPOSITION OF TOHMA STREAM (MALATYA - TURKEY) - Saler, Serap; Alış, Necla İpek (My University, 2016)
This study was completed with periodical surveys in Tohma Stream between April 2013- May 2014 period seasonally. During the study, a total of 32 species (22 belong to genus Rotifera, 8 to Cladocera and 2 Copepoda) were identified in Tohma Stream. During the study period, Keratella cochlearis (Rotifera), was found in every station in all seasons. Also, it was found that the most common family in the study was Brachionidae (8 species) from Rotifera. All of the zooplanktonic species have been detected for the first time in Tohma Stream.
Keywords: Deniz ve Tatlı Su Biyolojisi